Assessing Extraction Methods and Mechanical and Physicochemical Properties of Algerian Yucca Fibers for Sustainable Composite Reinforcement - Mohamed Amine Kacem; Moussa Guebailia; Nassila Sabba; Said Abdi; Mahdi Bodaghi (Macromolecular Materials and Engineering)
Abstract The utilization of biofiber in recent years has significantly increased due to its advantages like being environmentally friendly, availability, and low costs. This paper investigates the physicochemical, mechanical, and morphological properties of the yucca fiber extracted by three methods such as water‐retting, traditional, and chemical methods. These analyses are designed to evaluate the extraction methodology and the hypothesis of the influence of harvesting location and growth conditions of the fiber. Various technologies are used, such as SEM, FTIR, XRD, and tensile tests. The fiber extracted by water retting is the strongest in the mechanical analysis with a strength of 690.48 MPa, followed by fiber extracted with the traditional method with 685.48 MPa, also 673.06, 657.94, 373.68 MPa for the fiber extracted by the chemical method using 3%, 5%, 10%NaOH respectively. The fiber obtained by the water retting method also has a higher chemical composition with 80.25% cellulose, 10.45% lignin, and 13.75% hemicellulose. The morphological characteristics are examined using Scanning Electron Microscopy. The crystallinity index ranged from 61.75% to 70.77%, and crystallite size from 1.73 to 2.04 nm is calculated from the XRD analysis. All these results confirm that yucca fiber can be a good sustainable choice for composite reinforcement.